Armed conflict and mental health in Colombia. (2019)
Although significant progress has been made in the peace process, Colombia still experiences high levels of ongoing violence and a legacy of more than five decades of armed conflict. Epidemiological studies show markedly raised levels of mental health problems in people affected by the conflict, with internally displaced people being a large and important group with unmet needs. Provision of mental health services is uneven and subject to significant underinvestment. Priority mental health treatment for victims of the conflict is now established in law, although the effectiveness of these programmes has yet to be established.